System of Values and Sufis (The Image of Values and Sufis in the First Epics of "Khamsa") - Muslikhiddin Kutbiddinovich, Mukhiddinov; Shoira Fatkhiddinovna, Kutbitdinova (International Journal of Psychosocial Rehabilitation, 2020)
Man should always give thanks to his Lord and follow his right path, practice the Shari’a, strengthen his faith in prayer, believe in the power and existence of the eternal God, and fulfill his duty. These are the attributes of a believing Muslim. In the eyes of Islam, this perfect man is also a devout, pious, upright, honest person who adheres to the rules of Shari’a and follows the Qur’an and the Sunnah. But in the eyes of the mystic, the perfect man must have the teachings and the truth along with the Shariah, that is, the Sufis have been living on the path of mathematics, not passing the status of the teaching, burning the worldly possessions, their own desires, and even their own self. They say that Hezr, Jesus, Gabriel, Makoel, and Azril are all full of qualities and attributes. This is an ideal. The supreme example of human perfection. This is evident from the fact that there is a convergence between the concept of a perfect person and the concept of an ideal person (a dream person). Ideal human characteristics are embodied in oral examples of heroic epics. Romantic artworks also portray an ideal human being (heroic, supernatural). This is the reason why poetry is so popular in poetry. There is a similarity between the characteristics of perfect human beings and those of the prophets and the saints. However, the people of mysticism unanimously refer to Prophet Muhammad (peace be upon him) as an example of perfection. If the Prophet (peace and blessings of Allah be upon him) is an example of excellence, then the guardians are the ones who will follow him. The Walîs also have different levels of steps, ranging from polar to abstract. Thus, the sheikhs are the murshids, the noble pirates, the arif, and the righteous, and the dervish-Sufis are the ones who have attained the rank of perfection. Man is impeccable, especially when the world and the devil’s lust entangle him and mislead him. Therefore, the path of perfection is to destroy the nafs and gain enlightenment.